2020
DOI: 10.1177/1079063220940305
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Risk Factors Among Discharged Military Veterans and Civilians Involuntarily Hospitalized Under California’s Sexually Violent Predator Act

Abstract: While military veterans have a lower overall rate of incarceration for criminal offenses than civilians, they have a higher rate of incarceration for violent sexual offenses. Despite military veteran overrepresentation among individuals adjudicated for violent sexual offenses, little is known about their risk factors for sexual offending. This study compared military veterans and civilians who had been involuntarily hospitalized and discharged pursuant to California’s Sexually Violent Predator Act. Pedophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We used the data set as detailed by Paden et al (2021) and Azizian et al (2022); the methods are as described within these published articles. As detailed within these prior publications (Azizian et al, 2022; Paden et al, 2021), institutional review board (IRB) approval was obtained from the California Committee Protection of Human Subjects, which serves as the IRB for all California state agencies. The study also underwent review by the California State Hospital Research Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the data set as detailed by Paden et al (2021) and Azizian et al (2022); the methods are as described within these published articles. As detailed within these prior publications (Azizian et al, 2022; Paden et al, 2021), institutional review board (IRB) approval was obtained from the California Committee Protection of Human Subjects, which serves as the IRB for all California state agencies. The study also underwent review by the California State Hospital Research Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Reference is made to the data coding and entry procedures as detailed in Paden et al (2021). SVP evaluations are conducted independently by two evaluators (primarily psychologists) designated by the California Department of State Hospitals to perform such evaluations (Weinberger et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of high-risk sexual offenders released from sexually violent predator commitment, found that military veterans, when compared to civilians, were more likely to target male victims under age 13, were almost twice as likely to have a pedophilic disorder than their civilian counterparts, and had high rates of childhood sexual trauma (Paden et al, 2021). Veterans with sexual trauma history have higher odds of committing a sexual offense than other offenses (Finlay et al, 2019).…”
Section: Specialized Treatment For Sexual Deviancymentioning
confidence: 99%
“…One found that military veterans with a history of multiple sexual offenses (more than one victim) tended to have male victims, histories of alcohol abuse, childhood physical trauma and Post Traumatic Stress Disorder (PTSD; Brooks Holliday et al, 2021). Another study of high-risk sexual offenders released from sexually violent predator commitment, found that military veterans, when compared to civilians, were more likely to target male victims under age 13, were almost twice as likely to have a pedophilic disorder than their civilian counterparts, and had high rates of childhood sexual trauma (Paden et al, 2021). Veterans with sexual trauma history have higher odds of committing a sexual offense than other offenses (Finlay et al, 2019).…”
Section: Upstream Va Policy Shiftmentioning
confidence: 99%